Hydro‐Biogeochemical Controls on Nitrate Removal: Insights From Artificial Emergent Vegetation Experiments in a Recirculating Flume Mesocosm - B. R. Waterman; A. T. Hansen (Water Resources Research)
Abstract Environments with aquatic vegetation can mitigate excess nitrogen (N) loads to downstream waters. However, complex interactions between multiple hydro‐biogeochemical processes control N removal within these environments and thus complicate implementation of aquatic vegetation as a management solution. Here, we conducted controlled experiments using a canopy of artificial rigid emergent vegetation in a recirculating flume mesocosm to quantify differences in rates of mass transport and nitrate (NO3−N) removal between the open channel‐canopy interface across a range in nominal water velocities. We found NO3−N removal rates were 86% greater with the canopy present compared to no canopy control experiments and were always greatest at intermediate velocity (6 cms−1). With the canopy present, a hydrodynamically distinct mixing layer formed at the open channel‐canopy interface, and resources, such as carbon (C), CN ratios, and dissolved oxygen, differed between open channel and vegetated canopy. The dimensionless Damköhler (Da) number indicated NO3−N removal rates were reaction limited (Da << 1) for all canopy experiments, yet across all velocities NO3−N removal was more reaction limited in the open channel than the canopy due to higher rates of mixing and less contact time with reactive surfaces. We found significant relationships between NO3−N removal rates and Da with hydrodynamic metrics (mixing zone width and Reynolds number, respectively), suggesting that NO3−N removal in the presence of rigid vegetation can be enhanced by manipulating flow conditions. These findings demonstrate that rigid emergent vegetation‐open channel interfaces create conditions conducive for NO3−N removal and with effective management can improve overall water quality.